Single nano plastic detection method based on Raman spectrum technology

By sputtering Ag on the surface of the inverted pyramid structure of the silicon substrate to form a composite substrate, the problems of poor reproducibility of nanoplastics detection and insufficient signal stability in the prior art are solved, and efficient detection of nanoplastics as low as 360nm is achieved, with the advantages of high signal-to-noise ratio and high spectral quality.

CN119845918APending Publication Date: 2025-04-18FUDAN UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411766620.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing surface-enhanced Raman spectroscopy methods have problems such as poor reproducibility, difficulty in controlling signal stability, and insufficient spectrum quality in nanoplastic detection, making it difficult to achieve efficient detection of single-particle nanoplastics.

Method used

A silicon substrate inverted pyramid structure is adopted and Ag is sputtered on its surface to form a composite substrate for achieving surface-enhanced Raman spectral detection with high signal-to-noise ratio and high spectral quality.

Benefits of technology

This method can effectively detect nanoplastics with particle size as low as 360nm, improve the detection accuracy and reliability, and achieve high signal-to-noise ratio and high spectral quality detection effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119845918A_ABST
    Figure CN119845918A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental pollutant detection, and particularly relates to a single nano plastic detection method based on a Raman spectrum technology. The method is based on the surface enhanced Raman spectrum technology, the surface enhanced Raman substrate is a composite film obtained by sputtering Ag on an inverted pyramid structure composite substrate, and detection of nano plastic is achieved; the thickness of the sputtered Ag is 60-140 nm, and the preferable thickness of the sputtered Ag is 120 nm. During detection, an object to be detected is transferred to the composite substrate and detected under a Raman instrument, and a baseline and cosmic rays are deducted from an obtained spectrum to obtain a Raman signal of the nano plastic; and comparing the Raman signal peak with a standard spectrogram library to judge whether the nano plastic exists or not and judge the type of the nano plastic. The method disclosed by the invention is relatively good in universality, has the advantages of rapidness, accuracy, stability and the like, is good in Raman spectrum quality and high in signal-to-noise ratio, and can be used for effectively detecting the nano plastic in a food sample; good application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental pollutant detection, and in particular relates to a single nanoplastic detection method. Background Art

[0002] Nanoplastics face significant challenges in detection due to their small size and complex morphology. Although existing Raman spectroscopy technology has been applied to the detection of a variety of microplastics and nanoplastics, its effectiveness in nanoplastic detection is limited, mainly because when the particle size is close to or less than the diffraction limit, the chemical signal becomes unstable, resulting in a decrease in resolution efficiency. Based on this, surface-enhanced Raman spectroscopy has gradually developed into a powerful technology for nanoplastic detection.

[0003] Surface-enhanced Raman spectroscopy greatly enhances weak Raman signals through surface plasmon resonance, and has been verified in many nanoplastic detection studies. However, the existing surface-enhanced Raman spectroscopy method still has the following shortcomings, which restricts its widespread application. First, the traditional disordered surface-enhanced Raman spectroscopy substrate often has significant differences between batches, resulting in poor detection reproducibility. In particular, the surface plasmon coupling effect between metal nanoparticles will vary significantly with the different aggregation states of the particles, making it difficult to stably control the signal intensity. Since the surface plasmon coupling effect between metal nanoparticles in the disordered surface-enhanced Raman substrate varies greatly due to their aggregation state, it becomes complicated to determine whether a single nanoplastic is enhanced, and it makes the reproducibility of the surface enhanced Raman scattering (SERS) signal difficult. In addition, the preparation process of the disordered surface-enhanced Raman spectroscopy substrate is easily interfered by external factors, which is not conducive to mass production and application.

[0004] To improve the above problems, researchers have developed highly ordered metal nanostructure arrays prepared by electron beam lithography or nanosphere lithography to improve the stability of surface-enhanced Raman scattering substrates. For example, Xu et al. used commercial Klarite substrates to etch inverted pyramid structures on silicon wafers by photolithography and sprayed gold on the surface, significantly reducing the detection limit of nanoplastics to 360nm under laboratory conditions. However, the Klarite substrate is affected by the 520cm -1 and 960cm -1The strong background signal at the site inevitably interferes with the detection of nanoplastics. Therefore, the prior art still has deficiencies in high signal-to-noise ratio and signal reproducibility, and cannot achieve efficient detection of single-particle nanoplastics. In addition, the commercial Klarite substrate is expensive. The present invention optimizes the metal material and thickness design to propose a new surface-enhanced Raman spectroscopy substrate that can achieve high signal-to-noise ratio and high spectrum quality, so as to effectively overcome the deficiencies in the prior art and greatly improve the accuracy and reliability of single-particle nanoplastic detection. Summary of the invention

[0005] The present invention aims to solve the above-mentioned deficiencies in the prior art and to provide a method for detecting single nanoplastics with low cost, high speed, high signal-to-noise ratio and high spectral quality.

[0006] The single nanoplastic detection method provided by the present invention is based on surface enhanced Raman spectroscopy technology, wherein the surface enhanced Raman substrate adopts a silicon substrate inverted pyramid structure, and Ag is sputtered on the substrate surface to obtain a composite substrate to achieve the detection of nanoplastics.

[0007] In the composite substrate, the sputtering thickness of Ag is 1 nm-1000 nm, preferably the sputtering thickness of Ag is 60-140 nm, and more preferably the sputtering thickness of Ag is 120 nm.

[0008] The present invention provides a method for detecting a single nanoplastic. The object to be detected (such as a pre-treated environment, food or other sample) is transferred to the composite substrate and detected under a Raman instrument. The baseline and cosmic rays are subtracted from the obtained spectrum to obtain the Raman signal of the nanoplastic. The Raman signal peak is compared with a standard spectrum library to determine whether the nanoplastic exists and the type of the nanoplastic.

[0009] In the present invention, the peak position of the Raman signal related to nanoplastics is located at 200-3200cm -1 It is called a specific Raman peak signal, which is used as the basis for determining whether nanoplastics exist.

[0010] In the present invention, the principle of using a composite substrate sputtered with Ag is that standard Raman spectroscopy is usually difficult to effectively detect nano-scale microplastics, so surface enhanced Raman spectroscopy is required. By using an Ag-sprayed inverted pyramid composite substrate, Ag nanoparticles are evenly covered on the surface of the silicon substrate, which can achieve a SERS enhancement effect and effectively attenuate the Raman peak interference inherent in the silicon substrate. Therefore, an inverted pyramid structure substrate with a thickness of 1nm-1000nm (preferably 60nm-140nm) sprayed with Ag can be used as a substrate for SERS detection to detect nanoplastics.

[0011] The Raman peak interference inherent in the silicon substrate includes the Si-Si bond vibration peak (520 cm -1 -1) and the second-order Si Raman peak (960 cm -1 -1).

[0012] In the present invention, a composite substrate is obtained by sputtering Au, Ag, and Cu on the inverted pyramid structure substrate of the silicon substrate respectively, and the properties of the three metal composite substrates are compared and tested, including the signal-to-noise ratio of the Raman spectrum of the nanoplastics and the matching degree between the Raman spectrum of the nanoplastics and the standard Raman spectrum. The results show that (for example, when the sputtering thickness is 120 nm), the performance of the composite substrate sputtered with Ag is better than that of the composite substrates sputtered with Au and Cu; the principle is as follows: Visible light and Au, Ag, and Cu in III-V semiconductors are commonly used plasma materials for SERS, with low inherent losses, and the prerequisite resonance condition provided by the real part of the dielectric constant (ε′(ω)) being less than 0 at visible light frequencies. In the present invention, Au and Cu are further selected as the control metals for Ag to study characteristics such as the surface enhancement effect of the substrate. Compared with the substrates loaded with Au and Cu, the Raman spectrum of 360 nm PS on the substrate with an Ag-loaded structure has the highest signal-to-noise ratio and spectrum quality of the spectrum. Empirical evidence shows that in the visible light spectrum, the order of the imaginary part of the dielectric constant (ε″) is: Ag < Au < Cu. When the resonance condition is satisfied, the local electric field inside the nanoparticle is directly related to the imaginary part. The smaller the value of the imaginary part, the less loss generated by the polarization process, resulting in a stronger local electric field inside the nanoparticle and a more obvious enhancement effect. This also proves that the composite substrate sputtered with Ag is superior to the substrates sputtered with Au and Cu in detecting nanoplastics.

[0013] The detection method for a single nanoplastics provided by the present invention specifically uses a laser confocal Raman spectrometer system, which specifically includes an optical microscope, a laser light source, a sample device, a filter, a monochromator (or interferometer), a detector, etc.

[0014] The specific operation process is as follows:

[0015] (1) Transfer the pre-treated sample to the inverted pyramid structure composite substrate with an Ag spraying thickness of 1 nm - 1000 nm as the substrate for SERS detection, and place it on the sample device stage of the laser confocal Raman spectrometer system;

[0016] (2) Determine the position and size of the sample to be measured on the inverted pyramid structure composite substrate through the optical microscope, and accurately adjust the focal length;

[0017] (3) Turn on the laser light source and collect the Raman spectrum at the location of the sample on the inverted pyramid structure composite substrate;

[0018] (4) Compare the Raman spectrum of the sample with the standard plastic spectrum in the commercial database to determine whether there is nanoplastic, the specific type and the matching value;

[0019] (5) The signal-to-noise ratio of the nanoplastic Raman spectrum is calculated based on the Raman spectrum measured by the sample.

[0020] In the present invention, the nano plastics include polystyrene (PS), polymethyl methacrylate (PMMA) and the like, but are not limited thereto.

[0021] The SERS substrate used in the present invention can efficiently detect the Raman signal of nanoplastics. The substrate detects PS with a single size of 360nm, and its spectrum quality, that is, the matching degree with the standard spectrum reaches more than 80%, reaching or even exceeding the matching threshold for microplastic discrimination. PMMA with a single size of 360nm can also be effectively detected, and its spectrum quality, that is, the matching degree with the standard spectrum also reaches more than 80%. The matching threshold for microplastic discrimination is 60%-70%.

[0022] The invention has the beneficial effects that the use of the Ag-sprayed inverted pyramid structure composite substrate as a SERS substrate can achieve the purpose of efficiently detecting nanoplastics, and can realize the detection of nanoplastics with a particle size as low as 360nm. Spraying Ag increases the intensity of the Raman signal, which is better than spraying Au and spraying Cu, thereby ensuring that the nanoplastics can be effectively detected.

[0023] The method of the present invention has good universality and has the advantages of being cheap, rapid, highly accurate, precise, stable, etc. It can effectively detect nanoplastics in standard PS, standard PMMA and food samples. It has good application prospects. The application fields include environment, food, medicine, bioengineering, chemical engineering and scientific research. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a diagram of the single nanoplastic detection method of the present invention.

[0025] Figure 2 The matching degree between the Raman spectrum of a 360nm PS sphere on a 120nm Ag, Au and Cu substrate and the standard spectrum.

[0026] Figure 3 This is the signal-to-noise ratio of the Raman spectrum of a 360nm PS sphere coated with 120nm Ag, Au and Cu substrates.

[0027] Figure 4 This is the Raman signal of a PS ball with a size of 360nm measured on a substrate coated with 120nm Ag, Au and Cu.

[0028] Figure 5 The matching degree between the Raman spectrum of a PMMA ball with a size of 360nm and the standard spectrum measured on a substrate coated with 120nm Ag, Au and Cu.

[0029] Figure 6 This is the signal-to-noise ratio of the Raman spectrum of a 360nm PMMA sphere coated with 120nm Ag, Au and Cu substrates.

[0030] Figure 7 This is the Raman signal of a PMMA ball with a size of 360nm measured on a substrate coated with 120nm Ag, Au and Cu.

[0031] Figure 8 This is the Raman signal of nanoplastic No.1 released from a plastic lunch box measured on a 120nm Ag-plated substrate.

[0032] Fig. 9 This is the SEM image of nanoplastic No. 1 released from a plastic lunch box measured on a 120nm Ag-plated substrate.

[0033] Fig.10 This is the Raman signal of nanoplastic NO.2 released from a plastic lunch box measured on a 120nm Ag-plated substrate.

[0034] Fig.11 This is the SEM image of nanoplastic NO.2 released from a plastic lunch box measured on a 120nm Ag-plated substrate.

[0035] Fig.12 This is the Raman signal of a PS ball with a size of 1000nm under different Ag spraying thicknesses.

[0036] Fig.13 The PS ball is 1000nm in size, 1001cm under different Ag spraying thickness -1 and 520cm -1 Raman intensity. DETAILED DESCRIPTION

[0037] The method of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The protection scope of the present invention is not limited to the embodiments.

[0038] The specific steps for optimizing the Ag spray thickness, optimizing the metal spray type, and testing samples are as follows:

[0039] (I) Optimization of Ag spray thickness

[0040] (1) Use a pipette to take 2 μL of the 1000 nm PS standard sample diluted solution and drop it on the Ag-sprayed inverted pyramid structure composite substrate. Wait for the solution to dry;

[0041] (2) placing the dried Ag-sprayed inverted pyramid structure composite substrate on a sample device in a laser confocal Raman spectrometer system, and obtaining a clear image of a single microplastic standard sample by moving the stage of the sample device and focusing the objective lens of the optical microscope;

[0042] (3) Turn on the laser, select appropriate laser and acquisition parameters, and collect Raman signals of microplastics. The laser used is 532nm, the acquisition time is 10 seconds, and the number of acquisitions is 1. The same applies to other types of plastics;

[0043] (4) The Raman peak signal in the collected Raman spectrum is made into an image.

[0044] (II) Optimization of metal spraying type

[0045] (1) Use a pipette to take 2 μL of 360 nm PS and 2 μL of 360 nm PMMA standard sample diluted solutions and drop them on the inverted pyramid structure composite substrate sprayed with 120 nm Ag, the inverted pyramid structure composite substrate sprayed with 120 nm Au, and the inverted pyramid structure composite substrate sprayed with 120 nm Cu, respectively, and wait for the solutions to dry;

[0046] (2) placing the dried 120nm Ag-sprayed inverted pyramid structure composite substrate, 120nm Au-sprayed inverted pyramid structure composite substrate, and 120nm Cu-sprayed inverted pyramid structure composite substrate on a sample device in a laser confocal Raman spectrometer system, and obtaining a clear image of a single microplastic standard sample by moving the stage of the sample device and focusing the objective lens of the optical microscope;

[0047] (3) Turn on the laser, select appropriate laser and acquisition parameters, and collect Raman signals of microplastics. The laser used is 532nm, the acquisition time is 10 seconds, and the number of acquisitions is 1. The same applies to other types of plastics;

[0048] (4) The Raman peak signal in the collected Raman spectrum is made into an image.

[0049] (III) Sample testing

[0050] The steps for testing the samples are similar to the steps for optimizing the thickness of Ag spraying in this embodiment, and are as follows:

[0051] (1) Transfer the pretreated sample to a 120 nm Ag inverted pyramid structure composite substrate and wait for the solution to dry;

[0052] (2) placing a 120 nm Ag inverted pyramid structure composite substrate on a sample device stage in a laser confocal Raman spectrometer system, and obtaining a clear image of the nanoplastic particles by moving the sample device stage and magnifying and focusing the optical microscope objective lens;

[0053] (3) Turn on the 532nm laser, select the acquisition time as 10 seconds, the acquisition number as 1, and collect the Raman signal of the sample to be tested, so as to achieve the measurement of nanoplastics. The acquisition time and the acquisition number are not limited to this.

[0054] In order to improve the stability of nano plastic detection, the surface enhanced Raman technology based on the inverted pyramid structure composite substrate modified by nano Ag is adopted. The preparation steps of the inverted pyramid structure composite substrate modified by nano Ag are as follows: 60, 80, 100, 120, 140nm of Ag are sprayed on the front of the inverted pyramid structure composite substrate using a c magnetron sputtering instrument, and the SERS substrate for detecting micro plastics is obtained. The size of the silicon substrate layer is 4.0×4.0mm, the size of the inverted pyramid array unit is 2.5×2.5μm, the gap between the array units is 1.5μm, and the depth of the inverted pyramid is 1.77μm. The control group is an inverted pyramid structure composite substrate sprayed with Au and Cu. The inverted pyramid structure composite substrate modified by nano Ag is obtained. Fig.12 These are the test results under different Ag spraying thicknesses. Fig.13 PS is 1001cm under different spraying Ag thickness. -1 and 520cm -1 Raman intensity.

[0055] like Figure 1 As shown, the nanoplastic in the sample to be tested is transferred to the inverted pyramid structure composite substrate through the inverted pyramid structure composite substrate.

[0056] like Figure 2 , Figure 3 , Figure 5 and Figure 6 As shown, the SERS effect produced by nano-Ag greatly improves the spectrum quality and signal-to-noise ratio of Raman spectroscopy. This method can easily and very accurately detect nanoplastics with a minimum diameter of 360nm.

[0057] Compared with nanoplastic detection technology, the microplastic detection method based on inverted pyramid structure composite substrate and SERS technology is more convenient for the detection of nanoplastics, with high spectral quality, high signal-to-noise ratio, good accuracy and wide adaptability.

Claims

1. A method for detecting a single nanoplastic based on surface enhanced Raman spectroscopy, characterized in that: The surface enhanced Raman substrate adopts an inverted pyramid structure of a silicon substrate, and Ag is sputtered on the surface of the substrate to obtain a composite substrate to realize the detection of nanoplastics.

2. The method for detecting a single nanoplastic according to claim 1, characterized in that: In the composite substrate, the sputtering thickness of Ag is 1nm-1000nm.

3. The method for detecting a single nanoplastic according to claim 1, characterized in that: In the composite substrate, the sputtering thickness of Ag is 120 nm.

4. The method for detecting a single nanoplastic according to claim 1, characterized in that: The Raman signal peaks associated with nanoplastics are located at 200-3200 cm -1 It is called a specific Raman peak signal, which is used as the basis for determining whether nanoplastics exist.

5. The method for detecting a single nanoplastic according to claim 1, characterized in that: The laser confocal Raman spectrometer system is used, and the specific operation process is as follows: (1) transferring the pretreated sample to an inverted pyramid structure composite substrate and placing it on a sample device stage of a laser confocal Raman spectrometer system; (2) determining the position and size of the sample to be tested on the inverted pyramid structure composite substrate by an optical microscope, and accurately adjusting the focal length; (3) turning on the laser light source to collect the Raman spectrum of the sample on the inverted pyramid structure composite substrate; (4) Compare the Raman spectrum of the sample with the standard plastic spectrum in the commercial database to determine whether there is nanoplastic, the specific type and the matching value; (5) The signal-to-noise ratio of the nanoplastic Raman spectrum is calculated based on the Raman spectrum measured by the sample.

6. The method for detecting a single nanoplastic according to any one of claims 1 to 5, characterized in that: The nano plastics include polystyrene (PS) and polymethyl methacrylate (PMMA).

Citation Information

Patent Citations

  • Single micro / nano plastic detection method based on Raman spectrum technology

    CN112903655A

  • Composite surface-enhanced Raman substrate and preparation method thereof

    CN117949430A

  • Composite surface enhanced Raman scattering substrate

    CN211553757U

  • Substrate for surface enhanced raman scattering (SERS)

    US20110228266A1

  • Non-labeled virus detection substrate, system, and method based on inverted multi-angular cavity arrays

    US20120071352A1